2020
DOI: 10.1007/s12310-020-09368-9
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of School-Based Efforts to Support Students Who Have Experienced Trauma

Abstract: The current review sought to describe the published literature relative to addressing trauma in schools. Through a systematic review of peer-reviewed publications as well as gray literature, we identified a total of 91 publications that were coded for study rigor as well as a number of intervention characteristics. Publications included in the review mentioned a variety of intervention components, most notably an emphasis on counseling services, skill development, psychoeducation related to trauma, and parent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 84 publications
1
37
0
1
Order By: Relevance
“…Careful, contextually appropriate systematic practice should be the goal (Theron, 2016). A public health approach that addresses trauma in schools has great value (Overstreet & Mathews, 2011), but a recent review of school‐based efforts to address trauma revealed the limited number of whole‐school efforts and a lack of rigor in existing studies specifically those focused on students impacted by trauma such as those in foster care (Stratford et al, 2020). It is also important for schools to address the whole child.…”
Section: Discussionmentioning
confidence: 99%
“…Careful, contextually appropriate systematic practice should be the goal (Theron, 2016). A public health approach that addresses trauma in schools has great value (Overstreet & Mathews, 2011), but a recent review of school‐based efforts to address trauma revealed the limited number of whole‐school efforts and a lack of rigor in existing studies specifically those focused on students impacted by trauma such as those in foster care (Stratford et al, 2020). It is also important for schools to address the whole child.…”
Section: Discussionmentioning
confidence: 99%
“…Even for schools that do take steps to create trauma-informed environments, evidence of effectiveness is still limited. 19…”
Section: Training For School Staff On Traumamentioning
confidence: 99%
“…Rather, many resources highlighted connections between multi-tiered systems of support (MTSS) such as positive behavior intervention in schools (PBIS) and trauma-informed efforts, a trend that was highlighted in other recent reviews. 19,45,46 These frameworks, which are similar to the public health model for prevention and intervention, call for whole-school approaches (tier 1) as well as supportive and clinical intervention strategies (tiers 2 and 3) for those who are at risk for or experiencing trauma symptoms. The vast majority of states (40 as of 2019) encourage or require schools to implement MTSS, but few states do so with an explicit frame toward trauma.…”
Section: School-based Trauma-informed Framework and Programsmentioning
confidence: 99%
See 2 more Smart Citations